Health professionals' views of newborn pulse oximetry screening in a midwifery-led maternity setting. "It's a good thing to do, but fund it!". (February 2020) - Ward, Kim; Dixon, Lesley; Cloete, Elza; Gentles, Tom; Bloomfield, Frank; ,
Highlights: Maternity professionals support newborn oximetry screening to detect hypoxaemia. Under-resourcing will hinder successful universal newborn oximetry screening. Workload and remuneration need addressing when planning future newborn screening. Abstract: Objective: To understand from health professionals who care for newborns their views on the introduction of pulse oximetry screening for the detection of hypoxaemia in a midwifery-led maternity setting. Although oximetry screening for newborns is internationally accepted, national screening is not yet introduced in New Zealand. In this context, we drew on maternity carers' reflections during a feasibility study of oximetry screening to provide perspectives on barriers and enablers to universal screening. Methods: Data were generated from nine focus groups during five months of 2018 in two north island regions of New Zealand. Participants' ( n  = 45) opinions about the use of oximetry screening in newborns were analysed thematically using an inductive approach. Findings: Overall, participants stated pulse oximetry screening was easy to do, non-invasive, and worthwhile. Midwives were reassured by screening that provided evidence of either a healthy baby or a need for urgent review. From participants' reports, we identified three themes: (1) oximetry screening for newborns is reassuring, practical and worthwhile; (2) midwifery services workload expectations and under-resourcing will hinder universal screening, and (3) location of the baby at the time of screening could impede universal access. Conclusion and implications for practice: Midwives viewed implementing a national pulse oximetry screening programme as sensible but problematic unless resourced and funded appropriately. Policymakers should view the concerns of midwives about human and physical resources as significant and account for the need to resource this screening programme appropriately as a priority before implementation.